Some People Are Ostriches - Where Roofs Are Concerned - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet begins by comparing humans to ostriches; ostriches don't worry about what they can't see, much like humans don't often worry about their roofs. Discusses the importance of maintaining one's roof. For example, regularly painting wooden shingles avoids their tendency to curl and blow away. Describes other types of roofs, their maintenance, and a brief history of the bituminous coatings. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Roofs--Maintenance and repair; Paint materials; Bituminous materials; Oilseeds; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Roofing